Analysis of environmental education instruments in waste management at a university - Rodrigues, Ana Flávia da Silva; Marques, Evely Laranjeira; Alves, Rodrigo Couto (Brazilian Journal of Production Engineering, 2024)
Universities are responsible for the professional training of citizens, they are the ones who will qualify them to guarantee their performance in the different segments existing in the job market, therefore, their role in the socio-environmental trajectory is indisputable. Environmental education (EA) is an essential tool to raise awareness and sensitize people. This study aimed to analyze the impact of applying two EA instruments - lecture and digital booklet - on raising awareness among the academic community about waste management in a higher education institution (HEI). The results highlighted a significant increase in awareness and attitudes towards appropriate waste management, demonstrating that the interventions not only informed, but also inspired behavioral changes among participants. It is concluded that the implementation of EA strategies can effectively promote sustainable practices, contributing to improvements in waste management and strengthening the academic community's commitment to sustainability.
Keywords: Environmental Education; Solid Waste; Higher Education Institution